The Influence of Hearing Impairment on Mental Age in Down Syndrome: Preliminary Results - Saksida, Amanda; Brotto, Davide; Pizzamiglio, Giulia; Bianco, Elena; Bressan, Sara; Feresin, Agnese; Bin, Maura; Orzan, Eva (Frontiers in Pediatrics, 2021)
The increased life expectancy for patients with Down Syndrome (DS) has elicited the need to improve their quality of life by enhancing functional outcomes and identifying the factors that contribute to their long-term cognitive decline. Although the majority of individuals with DS have issues with hearing impairment (HI) since early childhood, to our knowledge no study has investigated whether HI represents a potential modulator of cognitive decline over time. The present explorative cohort study, albeit very preliminary due to the limited cohort (17 children), highlights the significant relation of a significant HI not only with receptive language abilities, but also with mental age in young patients with DS. Additional studies are required to confirm the link between HI and mental age and to assess the impact of audiological treatment on the enhancement of functional outcomes and of cognitive decline in individuals with DS.